PROFIL KETAHANAN PANGAN KABUPATEN JEMBRANA 2017 - Hertog Nursanyoto (Jurnal Skala Husada : The Journal of Health, 2018)
Abstract. The agricultural and plantation sectors are still the main economic support in Jembrana. Potential commodities that include coconut, coffee, cloves, cacao, and vanilla. Although Jembrana has been known as plentiful food production area, but food security study in Jembrana never done. This research is a cross sectional study conducted for 6 months in 10 selected villages namely Warnasari and Tuwed villages in Melaya; Tegal Badeng Barat and Baler Bale Agung in the Negara; Budeng and Yeh Kuning in Jembrana; Pohsanten and Delod Berawah in Mendoyo; and also Gumrih and Pulukan in Pekutatan. From each village was selected by simple random sampling of 20 households to obtain the total sample as a whole, amounting to200 households. From the result, it is known that the energy accessibility of Jembrana population reach 3669,64 kcal/capita/day, or about 166,8% AKE. As for the accessibility of protein reached 160,96 g/capita/day or nearly three-fold (282.39% AKP). The energy consumption is 2174,37 kcal/capita/day (101,13% AKE). While the protein consumption was 71.65 g/capita/day (125,7% PPA) with an average food desirable pattern  score (PPH) of 90,06. It can be concluded that the food consumption pattern of Jembrana Regency in 2017 quantitatively has been good, but qualitatively still not fulfill the national target. Some current problems and possibilities that occur in the future namely: a) The energy consumption, and especially the protein consumption of Jembrana district in 2017 has exceeded; b) Food security study is necessary every year to monitor the accessibility and level of energy and protein consumption of Jembrana residents. Keywords: Food Security, Level of Conssumption, Food Desirable Pattern